PROBLEMS AND PROSPECTS OF DEVELOPMENT OF THE REGIONAL ECONOMY OF TRANSCARPATHIA - BAKAY, VITALIY (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the state and problems of development of the regional economy of Transcarpathia. The peculiarities of the functioning of the regional economic complex in terms of its individual sectoral and territorial subsystems are outlined. Possible options, opportunities and directions of stimulating regional development in order to ensure its socio-economic growth are formulated and analyzed. The problems of economic development of the region are singled out, among which it is necessary to note: uneven economic and social development of the region; insufficient density and ramifications of relations between regions; low level of cooperation and interaction between regional and territorial entities; lack of clear implementation of strategic plans and programs, etc. It is proved that the problems of regional economic development are common problems for all regions of Ukraine. But at the same time, each region, focusing on its own resources and potential, must modernize the economy, using and building its own unique capabilities, based on endogenous factors of regional economic development. It is determined that the main branches of production specialization of Transcarpathia are food industry, light, forestry and woodworking industry, chemical, building materials industry and mechanical engineering. An important role belongs to trade in goods and services with EU countries, which are Ukraine’s main trading partners. Transcarpathia’s foreign economic activity is fully focused on the European Union market. Stimulation of regional development is considered through the prism of priority activities for the Transcarpathian region: activation of industry on an innovative basis, agriculture, tourism, development of border infrastructure, etc. It was found that the main source of stimulating the development of the region remains the state and partly local budgets, but it is not specified from which sources these funds will come and who will be their main administrator.